2020
DOI: 10.1080/01924036.2020.1732435
|View full text |Cite
|
Sign up to set email alerts
|

Contested gendered space: public sexual harassment and women’s safety work

Abstract: Feminist research and activism has along history of engaging with the range and extent of men's intrusive practices on women in public, taking as itsstarting point public space as aplace where gender relations are contested. Here, the impact of men's practices on women and girls is understood not only in terms of their safety, but also their freedom, highlighting how the "safety work" mandated for women and girls in public functions to limit women's space for action and responsiblise them for preventing violen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 29 publications
1
53
0
2
Order By: Relevance
“…Dolayısıyla kadınlar için kamusal mekânda şiddet korkusu ve deneyimi son derece cinsiyetlendirilmiş olup, bu korku bir temele dayansın ya da dayanmasın bireyselden ziyade toplumsal (ve aynı zamanda mekânsal) olarak inşa edilir. Bu anlamda, "cinsel taciz kadınların kamusal yaşamdan daha geniş anlamda dışlanmasını pekiştirme ve yeniden üretme işlevi gören ataerkilliğin mekânsal bir ifadesi olarak anlaşılabilir (Vera-Gray ve Kelly, 2020). "…”
Section: Kamusal Mekân Ve Toplumsal Cinsiyet Bağlamında Kadınların Kent Hakkıunclassified
See 1 more Smart Citation
“…Dolayısıyla kadınlar için kamusal mekânda şiddet korkusu ve deneyimi son derece cinsiyetlendirilmiş olup, bu korku bir temele dayansın ya da dayanmasın bireyselden ziyade toplumsal (ve aynı zamanda mekânsal) olarak inşa edilir. Bu anlamda, "cinsel taciz kadınların kamusal yaşamdan daha geniş anlamda dışlanmasını pekiştirme ve yeniden üretme işlevi gören ataerkilliğin mekânsal bir ifadesi olarak anlaşılabilir (Vera-Gray ve Kelly, 2020). "…”
Section: Kamusal Mekân Ve Toplumsal Cinsiyet Bağlamında Kadınların Kent Hakkıunclassified
“…Bu durum kadınları marjinal bir konuma iterek kent hayatından dışlanmasına ve kamusal mekanlara ait hissetmemesine neden olur -ki bu da kent hakkı ihlalinin kadınlar için gündelik bir pratik olması anlamına gelir (Fenster, 2005). Dolayısıyla kadınlar gündelik hayatlarında ancak bu "cinsiyetlendirilmiş faaliyet"ten kurtularak kamusal mekânları kendi şartlarına göre özgürce kullanıp aidiyet geliştirdikleri zaman kent hakkını tam anlamıyla gerçekleştirmiş olurlar (Vera-Gray ve Kelly, 2020).…”
Section: Kamusal Mekân Ve Toplumsal Cinsiyet Bağlamında Kadınların Kent Hakkıunclassified
“…Women routinely expend cognitive, emotional, and bodily labor in public spaces to manage their overwhelming fear of violent crime. Women's routine safekeepingtermed "safety work" in the research literature-includes behaviors such as being vigilant and alert, avoiding activities that occur after dark, and altering facework, body language, and clothing in public spaces to deter unwanted attention from men (Kelly, 1988;Rader, 2008;Vera-Gray, 2018;Vera-Gray & Kelly, 2020). While the effects of such strategies on women's vulnerability to violent crime and subjective perceptions of safety are unclear (Scott, 2003;Thompson, 1993), women's safety work is linked to a number of negative outcomes, including increased anxiety in public (Maxwell et al, 2019), restricted occupational possibilities (Laniya, 2005), and remaining in dependent relationships with men because they do not feel safe navigating public spaces alone (Pain, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these practical issues, it has been suggested that the implementation of poorly-designed gender-neutral toilets fails to recognise women's experiences of and fears about public spaces (Greed, 2019). Women can experience heightened levels of fear for themselves and their children in public spaces, specifically concerning the risk of physical and sexual violence and harassment (Pain, 1997;Vera-Gray and Kelly, 2020). The gendered nature of the fear of crime has often been framed as paradoxical: it has been contended that women experience higher levels of fear of victimization than men do but experience lower levels of actual victimization (Hale, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The gendered nature of the fear of crime has often been framed as paradoxical: it has been contended that women experience higher levels of fear of victimization than men do but experience lower levels of actual victimization (Hale, 1996). This apparent paradox has been challenged on a number of grounds, notably that experiences of sexual harassment are routinely excluded from victimization surveys (Vera-Gray and Kelly, 2020). In this sense, sexual harassment and violence act as a mechanism of control by which women's movement in public spaces and their engagement in public life are curbed (Kelly, 1998).…”
Section: Introductionmentioning
confidence: 99%